Possession, power and the new age: ambiguities of authority in neoliberal societies - Wood, Matthew (Theology and religion in interdisciplinary perspective series, 2007)
Approaching New Age -- The field of New Age studies -- Power, self and practice -- The meditation group -- Channelling workshops -- The Nottinghamshire fair -- Spiritualism and paganism -- Nonformativeness, possession and class in neoliberal societies